Record of intermediate-depth subduction seismicity in a dry slab from an exhumed ophiolite - Pennacchioni, G.; Scambelluri, M.; Bestmann, Michel; Notini, L.; Nimis, P.; Plümper, O.; Faccenda, M.; Nestola, F. (Earth and Planetary Science Letters, 2020)
The ophiolitic peridotite and gabbro of Moncuni (Southern Lanzo Massif, Western Alps) retain pre-subduction mantle-to-oceanic, high-temperature (>700C∘) ductile fabrics. These fabrics are overprinted by seismic fracturing and faulting associated with pseudotachylytes. Within the gabbro, the pseudotachylytes preserve dry glass and pristine microlites. The occurrence of rare, minute garnet and the static development of eclogite-facies assemblages in local hydrated domains indicate that pseudotachylytes experienced subduction conditions of 600C∘ and 2.1 GPa. The exceptional survival of glass and the absence of post-oceanic ductile deformation demonstrate prevailing dry conditions during the entire Alpine subduction and exhumation path. Dry conditions inhibited reaction kinetics and viscous flow. In contrast, the majority of the Alpine ophiolites, derived from the upper hydrated portions of the oceanic lithosphere, show pervasive fluid-assisted metamorphism and ductile deformation. The Moncuni body can, therefore, be regarded as representative for the rheological behaviour during subduction of seismic, dry, deeper oceanic lithosphere that is rarely exhumed to the Earth's surface. In Moncuni, the brittle-ductile transition of dry oceanic rocks is constrained to be between 600 and 750C∘. This temperature range corresponds to the observed cut-off of intermediate-depth seismicity within subducting slabs. We infer that the base of the seismic layer corresponds to the brittle-ductile transition of a dry slab rather than the locus of antigorite breakdown triggering earthquakes by dehydration embrittlement.
CRIS-Team Scopus Importer:2020-08-21
Keywords: earthquake; eclogite; fluids; ophiolite; pseudotachylyte; subduction